Director’s Advocacy Approach and Philosophical in Lancelot Oduwa Imasuen’s Invasion 1897 - Jacob Shimrumun Ioraa (CV. Rayyan Dwi Bharata, 2023)
The art of filmmaking is hinged on storytelling using visual and sound to communicate a massage to an audience. Of significant importance to the director and audience is the great impact of the film and its impartation on the audience which originates from an idea that brings about the story, giving impetus to a script then to a screenplay that plays a pivotal part in it. Yet the creative aspect both interpretative and technical is the sole responsibility of the director. He develops the vision, determine the look and throws up the thematic preoccupation using his creative capacity and ability to push the technique of narration of phenomena artistic level in order to take the audience to the original opinion in his advocacy approach. This paper tries to analyse the auteur style of Nigerian Lancelot Oduwa Imasuen of narration couch in flashback that is used in exploring his advocacy approach of philosophy. First, theory is explored through primary and secondary sources to offer a background and understanding of the advocacy approach and philosophy. Second, it investigates Invasion 1897 as case study through content analysis of the film and bring to the fourths in-depth usage of the technique that exposes the salient but important theme of advocacy of return. In examining the Nigerian film, this paper observes that the Auteur theory and not the writer or collaborative theories promote and project the director, Lancelot, as the author of his film who find an artistic angle to direct the screenplay into an effective epic and sets the film in a philosophical cradle. To continue with this discourse there are three great quotations that gives direction: ‘’ The real human drama of our lives is the key to filmmaking ‘’ (Antoine Frequa qtd. in Afolabi, 2005: 36); ‘’The most important skill that a director needs is a sense of story; how to tell a story’’ (George Roy Hill qtd. in Afolabi, 2005:27); and ‘’Directing is knowing the concept you want and getting it ‘’ (Clint Eastwood qtd. in Afolabi, 2005:27).